Assessment of Atherosclerotic Cardiovascular Disease Risk in Hypertensive Patient at Dhulikhel Hospital - Humagain, Sanjaya; Pathak, Surya Raj; Koju, Rajendra Prasad (Journal of Nepalgunj Medical College, 2023)
Introduction: Cardiovascular disease is the leading cause of death worldwide and the burden of which is rising in low and middle-income countries. Atherosclerotic cardiovascular disease risk scoring is a part of treatment guideline for hypertension and dyslipidemia management.Aims: This study is carried out to for the assessment of atherosclerotic cardiovascular disease risk among hypertensive patient.Methods: Hypertensive patients presenting to outpatient department were assessed for atherosclerotic cardiovascular disease risk and the 10 years risk score calculation was done using American College of Cardiology/ American Heart Association pooled cohort equation.Results: Out of total 212 patients 103 were male and 109 were female. 70 (33.02%) patients were smoker. The average systolic BP was 152 ± 18 mm Hg. Out of all hypertensive patients 164(77.36%) were receiving treatment and 48(22.64%) were newly diagnosed. Total of 76 (35.8%) patients were diabetic, 14 newly diagnosed. Total cholesterol was in the range of 367 mg /dl to 68mg/dl with mean 190 ±35mg/dl. HDL cholesterol range was 15 mg/dl to 78mg/dl with mean 42 ± 12 mg /dl. 10 years atherosclerotic cardiovascular disease risk was < 5% in 51(24.06%), 5 to < 7.5% in 34(16.04%), 7.5 to < 10% in 68(32.08%), 10 to 15 % in 24(11.32%).Conclusion: From this study we can conclude that atherosclerotic cardiovascular disease risk among hypertensive population is considerable and risk score calculation should be a part of patient evaluation so that they can be managed appropriately and the future cardiovascular events can be prevented.